Student learning or the student experience: the shift from traditional to non-traditional faculty in higher education - Carlos Tasso Eira de Aquino; Pamela Allen; Deb Lawton; Paul Withey (Centro de Estudios Financieros, 2016)
Trends in higher education indicate transformations from teachers to facilitators, mentors, or coaches. New classroom management requires diverse teaching methods for a changing population. Non-traditional students require non-traditional faculty. Higher education operates similar to a traditional corporation, but competes for students, faculty, and funding to sustain daily operations and improve academic ranking among peers (Pak, 2013). This growing phenomenon suggests the need for faculty to transform the existing educational culture, ensuring the ability to attract and retain students. Transitions from student learning to the student experience and increasing student satisfaction scores are influencing facilitation in the classroom. On-line facilitation methods are transforming to include teamwork, interactive tutorials, media, and extending beyond group discussion. Faculty should be required to provide more facilitation, coaching, and mentoring with the shifting roles resulting in transitions from traditional faculty to faculty-coach and faculty mentor. The non-traditional adult student may require a more hands on guidance approach and may not be as self-directed as the adult learning theory proposes. This topic is important to individuals that support creation of new knowledge related to non-traditional adult learning models.